1998
DOI: 10.1016/s0002-9440(10)65545-9
|View full text |Cite
|
Sign up to set email alerts
|

New Isolation Technique to Study Apoptosis in Human Intestinal Epithelial Cells

Abstract: Apoptosis is critically important to development, tissue homeostasis, and the pathogenesis of various diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 44 publications
0
66
0
Order By: Relevance
“…More than 97% of the isolated cells were intestinal epithelial cells that were positive for cytokeratin. 38 Studies in our lab using flow cytometry confirmed that less than 3% of contaminating cells stained for the pan-leukocyte marker, CD45 (data not shown).…”
Section: Intestinal Epithelial Cell Isolationmentioning
confidence: 74%
See 1 more Smart Citation
“…More than 97% of the isolated cells were intestinal epithelial cells that were positive for cytokeratin. 38 Studies in our lab using flow cytometry confirmed that less than 3% of contaminating cells stained for the pan-leukocyte marker, CD45 (data not shown).…”
Section: Intestinal Epithelial Cell Isolationmentioning
confidence: 74%
“…38 Lengthwise sections of intestine were washed in 4°C Ca 2ϩ -and Mg ϩ -free Hanks Balanced Salt Solution. The tissue was transferred to CMF-HBSS containing 10 mmol/L dithiothreitol and 50 nmol/L calyculin A (Calbiochem) for 30 minutes, 4°C.…”
Section: Intestinal Epithelial Cell Isolationmentioning
confidence: 99%
“…We purified intestinal epithelial cells using a modification of a previously published method (80). Briefly, a fresh section of intestine was opened lengthwise and washed in 4°C Ca 2+ -and Mg + -free HBSS (CMF-HBSS).…”
Section: Methodsmentioning
confidence: 99%
“…When epithelial cells lose such contacts, a form of apoptosis results, which has been termed anoikis (1). Physiologically, anoikis is important in the regulation of cell number in the intestinal tract, where epithelial cells are shed from villus tips in the small intestine and from the intercrypt epithelium of the colon and die by anoikis (2,3). Pathophysiologically, resistance to anoikis has been associated with metastatic spread of carcinoma cells (4,5), which reflects the ability of malignantly transformed epithelial cells to evade apoptosis when deprived of extracellular matrix attachment during dissemination in lymph or blood.…”
mentioning
confidence: 99%